1999
DOI: 10.1104/pp.120.1.113
|View full text |Cite
|
Sign up to set email alerts
|

γ-Radiation Induces Leaf Trichome Formation in Arabidopsis1

Abstract: We observed induction of additional trichome formation on the adaxial surface of mature leaves of Arabidopsis after massive doses (1-3 kilograys) of ␥-radiation from cobalt-60. A typical increase in trichome number was observed in the seventh leaf when the full expansion of the fifth leaf was irradiated. Under normal growth conditions, trichome numbers on the adaxial surface of seventh leaf of the Arabidopsis ecotypes Columbia (Col) and Landsberg erecta (Ler) were 122.5 ؎ 22.7 and 57.5 ؎ 14.5, respectively. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
(28 reference statements)
2
35
0
Order By: Relevance
“…It is reported that a weak allele of GL1, gl1-2, is normally glabrous but restores dense trichome formation in response to gamma-ray irradiation (Esch et al, 1994;Nagata et al, 1999). The reactive oxygen species (ROS) produced by water radiolysis are likely to be the inducers of trichome formation in irradiated gl1-2.…”
Section: Discrete Domains Of Gl1 Contribute To Trichome Induction Difmentioning
confidence: 99%
“…It is reported that a weak allele of GL1, gl1-2, is normally glabrous but restores dense trichome formation in response to gamma-ray irradiation (Esch et al, 1994;Nagata et al, 1999). The reactive oxygen species (ROS) produced by water radiolysis are likely to be the inducers of trichome formation in irradiated gl1-2.…”
Section: Discrete Domains Of Gl1 Contribute To Trichome Induction Difmentioning
confidence: 99%
“…With regard to drought, among the most possible indicators of water requirement in plant are stomata and trichomes (Adulrahaman, 2009). Drought may influence trichomes formation and structures of stomata (Nagata et al, 1999;Höglund and Larsson, 2005) Trichomes are hair-like appendages that develop from cells of the upper and lower epidermis found in most plant species (Werker, 2000). The structure of trichomes can range from unicellular to multicellular, and the trichomes can be straight, spiral, hooked, branched, or un-branched (Southwood, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that low dose gamma radiation provokes in plants: various physiological changes on the cellular level, 6 promoted expression of specific genes, e.g., those for antioxidative defense enzymes, 10-12 hormesis, 13 cross-adaptation to UV-B irradiation, high-intensity light, and drought stress, 11,14 increased biomass yield, plant vigor and growth, and grain yield, 11,[15][16][17] fruit ripening, 18 enhancements of embryogenesis, 19 and additional trichome formation. 8 The link between PGA and low dose gamma radiation-activated redox signaling cascades is implicated by the observation that the radiation induces drastic inhibition of PGA-decomposing enzyme polygalacturonase and the upregulation of pectin methylesterase, 18 thus Figure 1. the principles of low dose radiation-redox signaling conversion conducted by PgA in plants.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Even more, it has been shown that low dose gamma radiation-provoked trichome formation in Arabidopsis was prevented by the supplementation of antioxidants, and it has been proposed that the effects are mediated by reactive oxygen species generated by water radiolysis. 8 The transformation of the primary product of H 2 O 2 UV-lysis and water radiolysis -…”
Section: 9mentioning
confidence: 99%
See 1 more Smart Citation